2016
DOI: 10.18203/2394-6040.ijcmph20164717
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of anthropometric measurements of children attending urban and rural anganwadi centres of a coastal district in Karnataka, India

Abstract: Background: Malnutrition is defined as a pathological state resulting from a relative or absolute deficiency or excess of one or more essential nutrients. Weight for age, height for age and weight for height are usually used to describe the nutritional status of children. The present study was done to compare the anthropometric measurements of children attending urban and rural anganwadi centres.Methods: A cross sectional study was carried out in children aged three to six years attending 34 anganwadi centres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Out of 76.4% children who received supplementary nutrition, majority 49.4% of the children were of normal height for their age. [7][8][9] Whereas in this study it was observed that 30% of children had moderate stunting and 12% had severe stunting.…”
Section: Discussionmentioning
confidence: 46%
“…Out of 76.4% children who received supplementary nutrition, majority 49.4% of the children were of normal height for their age. [7][8][9] Whereas in this study it was observed that 30% of children had moderate stunting and 12% had severe stunting.…”
Section: Discussionmentioning
confidence: 46%